A dinuclear [{(p-cym)RuIICl}2(μ-bpytz˙−)]+ complex bridged by a radical anion: synthesis, spectroelectrochemical, EPR and theoretical investigation (bpytz = 3, 6-bis(3, 5-dimethylpyrazolyl)1, 2, 4, 5-tetrazine; p-cym = p-cymene). Issue 31 (20th July 2016) - Tripathy, Suman Kumar; van der Meer, Margarethe; Sahoo, Anupam; Laha, Paltan; Dehury, Niranjan; Plebst, Sebastian; Sarkar, Biprajit; Samanta, Kousik; Patra, Srikanta
Abstract : p -Cymene as an ancillary ligand favours the stabilisation of a tetrazine radical bridged in a dinuclear [{( p -cym)Ru II }2 (μ-bpytz˙ − )] + complex. Abstract : The reaction of the chloro-bridged dimeric precursor [{( p -cym)Ru II Cl}(μ-Cl)]2 ( p -cym = p -cymene) with the bridging ligand 3, 6-bis(3, 5-dimethylpyrazolyl)-1, 2, 4, 5-tetrazine (bpytz) in ethanol results in the formation of the dinuclear complex [{( p -cym)Ru II Cl}2 (μ-bpytz˙ − )] +, [1 ] + . The bridging tetrazine ligand is reduced to the anion radical (bpytz˙ − ) which connects the two Ru II centres. Compound [1 ](PF6 ) has been characterised by an array of spectroscopic and electrochemical techniques. The radical anion character has been confirmed by magnetic moment (corresponding to one electron paramagnetism) measurement, EPR spectroscopic investigation (tetrazine radical anion based EPR spectrum) as well as density functional theory based calculations. Complex [1 ] + displays two successive one electron oxidation processes at 0.66 and 1.56 V versus Ag/AgCl which can be attributed to [{( p -cym)Ru II C}2 (μ-bpytz˙ − )] + /[{( p -cym)Ru II Cl}2 (μ-bpytz)] 2+ and [{( p -cym)Ru II Cl}2 (μ-bpytz)] + /[{( p -cym)Ru III Cl}2 (μ-bpytz)] 2+ processes (couples I and II), respectively. The reduction processes (couple III–couple V), which are irreversible, likely involve the successive reduction of the bridging ligand and the metal centres together with loss of the coordinated chloride ligands. UV-Vis-NIR spectroelectrochemical investigation reveals typical tetrazine radical anion containing bands for [1 ] + and a strong absorption in the visible region for the oxidized form [1 ] 2+, which can be assigned to a Ru II → π* (tetrazine) MLCT transition. The assignment of spectroscopic bands was confirmed by theoretical calculations.